Validação experimental de um resfriador de água operando em ciclo de adsorção com aquecimento solar indireto - Araújo, Maria Elieneide (2009)
This work presents the experimental validation of a new adsorption solar refrigeration with indirect heating. The components of the refrigerator are: an adsorber, a condenser, an evaporator, and a solar collector. The choice of the adsorbate / adsorbent pair, water and silica gel type RD, respectively, took into consideration the temperatures reached by the solar collectors and available for the desorption of the refrigerant fluid (water) from the cavities of the adsorbent material (a porous solid). Due to the co-existence of the heating and cooling phases in the adsorber, a specific geometry for this component was defined so as to allow a good heat dissipation in the adsorbent material in the cooling phase, and the conservation of thermal energy in the heating phase. The experimental results validate the operation of the refrigerator, as temperature valves of 140ºC at the inlet of the adsorber, of 80ºC in the adsorber bed, and of 4,4ºC in the evaporator were reached, allowing its application in air conditioning systems